The World almanac and book of facts, 2014 - Janssen, Sarah 1982. (New York World Almanac Books, 2014)
Presents comprehensive facts and statistics on current events, people, and the countries of the world, along with original articles on recent issues and topics.
New in this edition: Marriage in the U.S.; The world at a glance; 2013 top 10 news topics; 2013 year in pictures (full-color).
Keywords: Almanacs, American; Statistics; United States -- Statistics